Utrophin influences mitochondrial pathology and oxidative stress in dystrophic muscle - Kennedy, T; Moir, L; Hemming, S; Edwards, B; Squire, S; Davies, K; Guiraud, S (BioMed Central, 2017)
Duchenne muscular dystrophy (DMD) is a lethal X-linked muscle wasting disorder caused by the absence of dystrophin, a large cytoskeletal muscle protein. Increasing the levels of the dystrophin-related-protein utrophin is a highly promising therapy for DMD and has been shown to improve pathology in dystrophin-deficient mice. One contributing factor to muscle wasting in DMD is mitochondrial pathology that contributes to oxidative stress and propagates muscle damage. The purpose of this study was to assess whether utrophin could attenuate mitochondria pathology and oxidative stress.Skeletal muscles from wildtype C57BL/10, dystrophin-deficient mdx, dystrophin/utrophin double knockout (dko) and dystrophin-deficient mdx/utrophin over-expressing mdx-Fiona transgenic mice were assessed for markers of mitochondrial damage.Using transmission electron microscopy, we show that high levels of utrophin ameliorate the aberrant structure and localisation of mitochondria in mdx mice whereas absence of utrophin worsened these features in dko mice. Elevated utrophin also reverts markers of protein oxidation and oxidative stress, elevated in mdx and dko mice, to wildtype levels. These changes were observed independently of a shift in oxidative phenotype.These findings show that utrophin levels influence mitochondrial pathology and oxidative stress. While utrophin deficiency worsens the pathology, utrophin over-expression in dystrophic muscle benefits mitochondria and attenuates the downstream pathology associated with aberrant mitochondrial function.